(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In our rapidly developing time, the internet has become a powerful information weapon, serving as an important factor in propaganda and propaganda of ideological and ideological threats on a global scale. With the help of social networks, special attention is paid to influencing the soul, consciousness and psyche of young people. As a result of this, youth spirituality continues to be derailed. Therefore, it is difficult for us not to ignore the escalation of various ideological, ideological and information attacks. Only then will we achieve the upbringing of a spiritually harmonious person, a healthy generation in perspective.